Analisis Yuridis Penegakan Hukum Tindak Pidana Pemalsuan Dokumen Sertifikat Vaksin Covid-19 - Anggraini, Fitria; Washliati, Laily; Prasetiasari, Christiani (Kajian Ilmiah Hukum dan Kenegaraan, 2022)
Article 263 Paragraphs (1) and (2) of the Criminal Code, and Article 35 of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE) regulates the crime of falsifying vaccine certificate documents. However, in Batam City there are still many criminal acts of falsifying vaccine certificate documents. In the Barelang Police, there are several criminal cases of forgery of vaccine certificate documents carried out by law enforcement. Purpose: The purpose of writing this thesis is to find out the legal arrangements for the criminal act of counterfeiting the Covid-19 vaccine certificate document, and to find out law enforcement, obstacles and solutions in dealing with the criminal act of counterfeiting the Covid-19 vaccine certificate document. Results: The results of the study show that legal arrangements for the criminal act of falsifying Covid-19 vaccine certificate documents are regulated in the Criminal Code, and Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions, as well as Law Number 4 1984 concerning Epidemic of Infectious Diseases which regulates criminal sanctions for makers of fake health documents and users of fake health documents may be sentenced to a maximum imprisonment of 9 (nine) years and/or a maximum fine of Rp. 3,000,000,000.00 (three billion rupiahs). Law enforcement in dealing with the criminal act of falsifying Covid-19 vaccine certificate documents has not run optimally, because those who are subject to penalties are imposed on the maker while the user of the vaccine certificate is not responsible. Limitations: The obstacles faced by the police in dealing with the criminal act of falsifying the Covid-19 vaccine certificate document are the forgery of the Covid-19 vaccine certificate is carried out in a structured and massive manner, the number of participants for the Covid-19 vaccine is very high, and the legal awareness of the public is low on the importance of vaccines. Contributions: The solution that can be taken by the police in dealing with the crime of falsifying Covid-19 vaccine certificate documents in Batam City is to improve coordination between the police and health workers, improve the performance of police officers in handling vaccine certificate counterfeiting, and increase socialization to the public about the importance of vaccines.